Poverty Status of Daily Wage Farm Labourers in Kilinochchi District - Umashankar, K.; Lojiny, T. (Faculty of Agriculture University of Jaffna, Sri Lanka, 2018)
Throughout the planet poverty is rampant. It is particularly marked in the developing world. Sri Lanka is no exception. Thirty years civil unrest in the North and East of Sri Lanka has totally destroyed the livelihood of the majority. This research was done in Kilinochchi to ascertain the poverty situations among the resident population In-Situ. Presently researchers say that acute poverty cannot be measured in monitory value alone. Rather it should have a multifaceted approach. Consequently, this research attempts to assess the poverty in Kilinochchi District using 'Multidimensional Poverty Index'. The researchers have arrived at the 'Deprivation Index' (DI) employing 'Multidimensional Poverty Index' (MPI). The target group selected for the research consisted of daily wage-earning farm labourers. Purposive random sampling was applied and 387 respondents were selected. A pretested structural questionnaire was adopted and data from this target group was elicited. In this research two factors relevant to health, two factors relevant to education and six factors relevant to living standards were considered to assess the poverty status. If the DI is 0.33 or more the subject is classified as in poverty. Results indicated 'Adjusted Head Count Index' (AHCI) to be 0.144 for Kilinochchi District. Among all 16 GN divisions in Kilinochchi District 'Konavil' and 'Periyaparanthan' are found to be the poorest. Next it is 'Muhamalai' followed by 'Oddupulam' and 'Alankerney' GN divisions. In comparison these GN divisions were seems to be more vulnerable than the others. The estimated AHC indices for these GN divisions are respectively 0.698, 0.554, 0.341, 0.259 and 0.206. The Sri Lankan Average Head count index is 4.1 %. In comparison all 16 GN divisions are found to be well above this index in Kilinochchi which indicates how urgent the poverty situation in Kilinochchi district is. Among the Kilinochchi GN divisions the least Head Count Index (HCI) is found to be in 'Jeyapuram' it being 12.5 %. Nevertheless, it is three-fold the national average. Based on the samples the research surmised the overall HCI for Kilinochchi District to be 32.9 %. The Department of Census and Statistics determined this Kilinochchi average as 18.2 % from their data. The Department says that this district is most poor in the Island. Be that as it may, though there is a discrepancy between the findings of researches and the Department of Census and Statistics values apparently due to the reduced number of respondents in the research venture it could be seen that the relevant district is the most poverty stricken in the Island. In retrospect, based on these inferences the researchers strongly recommend immediate commencement of action to the policy makers to address educational, health and living standards of the family units within the community in the Kilinochchi District
Keywords: Daily wage; Deprivation; Head Count Index; Kilinochchi; Poverty